2004
DOI: 10.1073/pnas.0408075101
|View full text |Cite
|
Sign up to set email alerts
|

The effect of midazolam on visual search: Implications for understanding amnesia

Abstract: The notion of multiple memory systems based on conscious accessibility has been supported largely by neuropsychological patient studies. Specifically, it was widely held that amnesic patients have impaired explicit memory performance but spared implicit memory performance. However, recent patient studies have called the implicit͞explicit memory distinction into question. In this study, normal participants were tested on a visual search task, once after an injection of midazolam, an anesthetic that induces temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
39
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 34 publications
(34 reference statements)
7
39
1
Order By: Relevance
“…We conclude that the critical medial temporal lobe structures related to amnesia serve the function of binding information together, regardless of whether that information is retrieved explicitly (declaratively) or implicitly (procedurally). Hence, as with other illustrations of impaired contextual learning in amnesia (Chun and Phelps, 1999;Park et al, 2004;Ryan et al, 2000), our findings do not support the idea that the hippocampus and medial temporal lobes control declarative memory alone.…”
Section: Discussioncontrasting
confidence: 90%
“…We conclude that the critical medial temporal lobe structures related to amnesia serve the function of binding information together, regardless of whether that information is retrieved explicitly (declaratively) or implicitly (procedurally). Hence, as with other illustrations of impaired contextual learning in amnesia (Chun and Phelps, 1999;Park et al, 2004;Ryan et al, 2000), our findings do not support the idea that the hippocampus and medial temporal lobes control declarative memory alone.…”
Section: Discussioncontrasting
confidence: 90%
“…Part of the evidence for hippocampal involvement was based on patients with damage to the HPC area that showed no advantage for repeated displays but still a strong improvement in performance with practice (Chun and Phelps 1999). This pattern was replicated with the drug midazolam that mimicked the results found with patients suffering from anterograde amnesia (Park et al 2004). Additional evidence for hippocampal involvement came from the fMRI study that showed that faster search times for repeated configurations corresponded to greater activation in HPC (Greene et al 2007).…”
mentioning
confidence: 58%
“…There has been some debate concerning the nature of the mechanism involved in the contextual cueing effect in terms of the brain regions engaged in the facilitation of search for repeated displays (Chun and Phelps 1999;Manns and Squire 2001;Park et al 2004;Greene et al 2007;Preston and Gabrieli 2008). Some researchers have argued that contextual cueing relies on hippocampus (Chun and Phelps 1999;Greene et al 2007), the region critical for associative memory.…”
mentioning
confidence: 99%
“…Thus, it appears that damage beyond the hippocampus is needed to impair perceptual learning in this task, and the available data do not contradict the idea that hippocampus-dependent memory is accessible to conscious recollection. Another study using the same task found that midazolam affected perceptual learning, particularly the learning of repeated displays (Park et al, 2004). However, the effects of midazolam are not limited to the hippocampus (Taguchi et al, 1989;Veselis et al, 1997), and they also extend to hippocampusindependent cognitive functions (Polster et al, 1993;Hirshman et al, 1999;Fisher et al, 2006).…”
Section: Discussionmentioning
confidence: 99%